Hubungan Kadar Hemoglobin Sebelum Operasi dengan Kebutuhan Transfusi Sel Darah Merah Intra Operasi pada Pasien Bedah Pintas Arteri Koroner di RSUD Abdul Wahab Sjahranie Samarinda: The Correlation between Preoperative Hemoglobin Level and Red Blood Cell Transfusion Intraoperative among Patients with Coronary Artery Bypass Graft at RSUD Abdul Wahab Sjahranie - Muhammad Akbar Rizqullah Rusydi; Ivan Joalsen Manggara Tua; Agustina Rahayu Magdaleni (Jurnal Sains dan Kesehatan, 2022)
Coronary Artery Bypass Graft (CABG) is a surgical procedure used to create bypass around the blocked coronary artery). Packed Red Cell (PRC) is required during CABG to balance hemoglobin level and the amount of red blood cell tranfused is basically estimated by observing preoperative hemoglobin level. Based on these reasons, the researcher aims to find the correlation between preoperative hemoglobin level and intraoperative red blood cell transfusion. The observational analytical design using cross sectional method was applied. The purposive non-probability sampling was used to select the research samples. Thirty-five samples fulfilling the inclusive and exclusive criteria were obtained. The findings revealed that patients’ preoperative hemoglobin level was normally transfused with 0 – 249 cc red blood cell for 18 intraoperative patients (51.4%). Patients’ preoperative hemoglobin level normally transfused with 250 – 500 cc red blood cell was only five patients (14.3%). The abnormally preoperative hemoglobin level transfused with 250 – 500 cc red blood cell was for 10 intraoperative patients (28.6%), whereas the abnormally preopreative hemoglobin level transfused with 0 – 249 cc red blood cell was only two patients (5.7%). It can be concluded that there is a correlation between preoperative hemoglobin level and intraoperative red blood cell transfusion with p value = 0.000 (p <0,05).